Genetic variability studies in the underutilized vegetable Momordica cymbalaria Hook F. - Rajamanickam, C; Arunachalam, P; Gnanasekaran, M; Sankar, C; Vijay, S K S; Vijayasamundeeswari, A; Sangeeth, S S S S (Plant Science Today, 2026)
The study aimed to examine the genetic variability and relatedness among 23 genotypes of athalakkai (Momordica cymbalaria Hook F.) evaluated at the college orchard, Department of Horticulture, Agricultural College and Research Institute, Madurai, Tamil Nadu. The study assessed yield-related traits such as days to sprouting, vine length, number of vines per plant, fruit stalk length, number of fruits per vine, number of fruits per plant, fruit length, fruit girth, fruit weight, number of seeds and yield per plant. Results showed significant variations in the mean performance of 23 athalakkai genotypes for various traits, indicating substantial genetic diversity and high breeding potential within the germplasm. The study of genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) in M. cymbalaria germplasms showed variability in traits such as fruits per vine, number of seeds, number of fruits per vine, number of vines per plant, vine length and yield per plant. High heritability estimates and genetic advance were observed, indicating that variation is due to a high degree of additive effect and can be improved through selection. Correlation and path analysis results showed that vine length, number of seeds, number of fruits per plant, number of fruits per vine, fruit weight and fruit stalk length had a significant positive direct effect on the number of fruits per plant, suggesting these traits could be considered for yield improvement programs in M. cymbalaria.